An investigation of the flexion relaxation ratio in adults with and without a history of self-reported low back pain and transient sitting-induced pain. (December 2022) - Mackey, Sarah; Howarth, Samuel J.; Frey, Mona; De Carvalho, Diana
Abstract: It is unknown whether the presence of sitting-induced pain or a clinical history of low back pain (LBP) changes spine function outcomes such as the flexion relaxation ratio (FRR). The purpose of this investigation was to determine whether sitting-induced pain or a history of non-specific LBP results in a different FRR. Forty-seven participants were instrumented with surface electromyography over erector spinae at L1, and accelerometers at L1 and S2. Standing maximum lumbar flexion trials were taken preceding and following a 1-hour sitting trial. Pain ratings during sitting and history of LBP were used to group participants for analysis. FRR values taken after the sitting exposures were compared between those that did and did not develop pain during sitting. Baseline FRR values were compared participants with and without a history of LBP. No significant differences in FRR were found for either pain groups (p = 0.11) or clinical history (p = 0.85). Lack of differences may be due to participants not currently experiencing a clinical episode of pain when the ratio was measured and/or because 1-hour sitting exposure was not long enough to induce pain modulation. The findings suggest that neither sitting-induced pain development or clinical history need to be controlled to prevent confounding of FRR.